2000
DOI: 10.1093/humrep/15.3.604
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cancer in children born after in-vitro fertilization

Abstract: Evaluation of the long-term health of children born using in-vitro fertilization (IVF) provides important information to clinicians and consumers. Until very recently, there have been no published data on the incidence of cancer in children conceived as a result of IVF, despite a number of case reports of neuroblastoma in children conceived using fertility drugs. This study used a record-linkage cohort design to investigate the incidence of cancer in children born after IVF. The study included all conceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0
15

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 9 publications
1
57
0
15
Order By: Relevance
“…While some studies showed increased risks for all cancers 14 and for specific types of cancer, such as retinoblastoma, 15 neuroblastoma, 6 leukemia, [16][17][18] and hepatoblastoma, 19,20 others found no association. [21][22][23][24][25][26][27][28][29][30][31][32] However, the main part of these studies are characterized by small sample sizes, short follow-up periods and lack of information on the use of fertility drugs. 33 Additionally, a major problem in this field of research is disentangling the effects of fertility treatment from the potential effects of the underlying infertility.…”
mentioning
confidence: 99%
“…While some studies showed increased risks for all cancers 14 and for specific types of cancer, such as retinoblastoma, 15 neuroblastoma, 6 leukemia, [16][17][18] and hepatoblastoma, 19,20 others found no association. [21][22][23][24][25][26][27][28][29][30][31][32] However, the main part of these studies are characterized by small sample sizes, short follow-up periods and lack of information on the use of fertility drugs. 33 Additionally, a major problem in this field of research is disentangling the effects of fertility treatment from the potential effects of the underlying infertility.…”
mentioning
confidence: 99%
“…В обобщенном голландском исследовании [35], где были включены и дети, ро-дившиеся в период 2002-2007 гг., был отмечен не-значительный повышенный риск ретинобластомы. В исследовании авторов из Австралии [8] и система-тическом обзоре из Нидерландов [40] было доложе-но об отсутствии возрастания случаев возникнове-ния рака у детей, зачатых методом ЭКО, по сравне-нию с детьми из общей популяции. В крупном швед-ском исследовании, включающем 16 280 детей, зача-тых с использованием методов ЭКО, родившихся в период 1982-2001 гг., был обнаружен такой же риск развития рака, как и в основной популяции, но нео-жиданно были выявлены более высокие риски раз-вития гистиоцитоза (стандартизованное отношение инцидентностей SIR 5,6 CI 95% 1,8-13) [28].…”
Section: заболеваемость раком после экоunclassified
“…Cinq nouveaux cas ont été diagnostiqués entre novembre 2000 et février 2002, ce qui représente une augmentation du risque de 7,2%, ou 4,9%, selon que l'on considère que 1,0%, ou 1,5%, des enfants sont conçus par FIV aux Pays-Bas. Cependant, deux autres études ne font état que d'une légère [8] [9]. Plusieurs articles rapportent quant à eux une augmentation du nombre de syndromes liés à un défaut d'EG.…”
Section: Malformations Congénitales Anomalies Chromosomiquesunclassified